??????? ???????? ?? ??? ?????? ??????? "????? ???? Literary Structuralist of Imam Syafi’I “Al-‘Aibu Fiina” Poem - Fuadi, Khairul; Ayat Alsalih (El-Jaudah : Jurnal Pendidikan Bahasa dan Sastra Arab, 2024)
Abstrac: Imam Syafi’i is known for his eloquence in the Arabic language and his ability to use metaphors, similes and other literary styles to convey spiritual messages in a beautiful and effective way. One of his poems is about the weaknesses (faults) of human beings. The author aims to analyse “Al-‘Aibu Fiina” poem to understand its depth and uniqueness. The theory used in this analysis involves a literary structuralist approach, which emphasises the intrinsic elements of the text. In structural analysis, it is important to observe how the use of language and literary styles reinforce the themes addressed in this poem. The author uses library research methods to collect data related to the discussion. The results of the analysis indicate that the structure of the poem consists of harmoniously arranged verses, using rhyme in the science of eloquence, describing the author's spiritual journey from darkness to divine light. Religious and wisdom themes are implied through the distinctive use of metaphorical language, making it easily digestible for readers. These findings provide a deeper understanding of the brilliance of Imam Syafi’i's literary work and it's relevance in the context of Arab and Islamic culture. Keywords: Imam Syafi’I, literary structuralist, Arabic Poem ?????? ?????: ????? ?????? ??????? ??????? ?? ????? ???????? ??????? ?? ??????? ?????? ???????? ????????? ?????? ???? ??????? ??????? ???? ???? ?????. ??? ?????? ?? ?? ??? (????) ???????. ???? ?????? ??? ????? ????? "????? ????" ???? ??? ??? ???????. ?????? ??????? ????????? ?? ??? ??????? ?????? ?????? ?????? ???? ??? ??????? ???????? ????. ????? ?? ??????? ??????? ?? ?????? ????? ??????? ????? ???????? ?????? ?? ????? ????????? ???? ???????? ?????? ?? ??? ???????. ?????? ?????? ?? ??? ????? ????? ?????? ???? ???????? ???????? ?????????. ????? ????? ??????? ?? ???? ??????? ????? ?? ????? ????? ???? ??????? ??????? ??????? ?? ??? ???????? ??? ???? ???? ?????? ??????? ?? ?????? ??? ????? ??????. ????? ??????? ????? ???????? ?????? ???? ???? ??? ?????? ???? ???. ???? ??? ??????? ????? ????? ?????? ??????? ??????? ?????? ??????? ???????? ?? ???? ??????? ??????? ??????????. ??????? ?????????: ??????? ????????? ??? ?????? ???????? ????? ??????